2019
DOI: 10.14349/sumapsi.2019.v26.n1.6
|View full text |Cite
|
Sign up to set email alerts
|

Abuso online en el noviazgo y su relación con el abuso del móvil, la aceptación de la violencia y los mitos sobre el amor

Abstract: Resumen El presente estudio tiene como objetivo analizar la prevalencia y las diferencias en la frecuencia y cronicidad del abuso online en el noviazgo de acuerdo con distintas variables sociodemográficas. Además, se analiza su relación con los mitos del amor romántico, el abuso del móvil y la aceptación de la violencia. Usando una muestra de 1657 estudiantes universitarios, los resultados revelaron que el 43.3% de los encuestados fueron perpetradores y el 42% víctimas de al menos un comportamiento de abuso on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
2
21

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 23 publications
5
21
2
21
Order By: Relevance
“…Moreover, as one of the myths of romantic love includes the association of jealousy and love, the connection with cyber-control victimization could be closer. Relations between romantic myths and cyber DV victimization in young couples have been previously observed [23]. However, possible associations of cyber-control and cyber-aggression victimization with adolescents' beliefs in romantic myths of love have barely been explored.…”
Section: Myths Of Romantic Love and Cyber Dating Violence Victimizationmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, as one of the myths of romantic love includes the association of jealousy and love, the connection with cyber-control victimization could be closer. Relations between romantic myths and cyber DV victimization in young couples have been previously observed [23]. However, possible associations of cyber-control and cyber-aggression victimization with adolescents' beliefs in romantic myths of love have barely been explored.…”
Section: Myths Of Romantic Love and Cyber Dating Violence Victimizationmentioning
confidence: 97%
“…Cyber DV includes both behaviors that involve harming victims through direct attacks, e.g., threats, insults or disseminating private information, namely cyber-aggression, and forms of abusive control of victims to monitor their social relationships and what they are doing at any time, namely cyber-control [1,11,18,20,21]. Cyber-control behaviors toward partners are more frequent than cyber-aggression behaviors [20,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the lack of variance in age; the majority of studies included students who were only 18 years of age, with 25% being aged 19 years). Finally, another study showed opposite results, reporting that older people (> 24 years) were more likely to be victims of control [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies that have investigated Internet use report a significant association between more Internet use (i.e. more time spent online and using diverse online activities more) and an increased probability of encountering risky situations online, such as peer aggression (Martínez-Ferrer, Moreno & Musitu, 2018), cyberbullying (Gini, Marino, Xie, Pfetsch & Pozzoli, 2019), doxing (Chen, Cheung & Chan, 2019), cyber dating abuse (Víllora, Navarro, Yubero, 2019) or grooming (Gómez, Rial, Braña, Golpe & Varela, 2017). It is, therefore, reasonable to suggest that the use of online dating sites/apps, and the time spent on them, may increase the likelihood of being exposed or enacting ghosting and breadcrumbing.…”
Section: Research Gaps: Lack Of Empirical Studies On Ghosting Breadcrumbing and Online Dating Usementioning
confidence: 99%
“…© 2020 Escritos de Psicología Escritos de Psicología, 13,[46][47][48][49][50][51][52][53][54][55][56][57][58][59] …”
unclassified